2015
DOI: 10.4149/neo_2015_119
|View full text |Cite
|
Sign up to set email alerts
|

High cytoplasmic expression of SALL4 predicts a malignant phenotype and poor prognosis of breast invasive ductal carcinoma

Abstract: Sal-like 4(SALL4) is significant for maintaining self-renewal and pluripotency in embryonic stem cells, cancer cells and perhaps even cancer stem cells. The expression of SALL4 has been recorded in various kinds of cancers and is deemed to have a clinical value for diagnosis. However, little information on SALL4 expression has been illustrated in breast cancer. In this study, the expression of SALL4 was scrutinized by immunohistochemical analysis in breast invasive ductal carcinoma in a large cohort of 160 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…Interestingly, the ESC markers SOX2, OCT4, SALL4, pSTAT3, and NANOG, showed both nuclear and cytoplasmic expression. This novel finding in MDBMSCC is consistent with previous studies reporting on cytoplasmic expression of NANOG in cervical cancer ( 38 ) and SALL4 in breast cancer ( 39 ) cells, inferring cytoplasmic expression as a predictor of poor prognosis ( 39 ). The reasons for this are the topic of further investigation.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, the ESC markers SOX2, OCT4, SALL4, pSTAT3, and NANOG, showed both nuclear and cytoplasmic expression. This novel finding in MDBMSCC is consistent with previous studies reporting on cytoplasmic expression of NANOG in cervical cancer ( 38 ) and SALL4 in breast cancer ( 39 ) cells, inferring cytoplasmic expression as a predictor of poor prognosis ( 39 ). The reasons for this are the topic of further investigation.…”
Section: Discussionsupporting
confidence: 92%
“…Our data showed that inhibition of EGFR pathway resulted in the downregulation of SALL4, and knockdown of SALL4 affected the self-renewal properties of CSCs. The enrichment of cells with CSCs markers (CD44 high /CD24 low ) and phenotypes in Erlotinib resistant NSCLC cell lines has been reported 32 , 35 . These observations suggest that CSCs was also selected during prolonged exposure to EGFR TKIs and contribute significantly to drug resistance and tumor relapse.…”
Section: Discussionmentioning
confidence: 98%
“…Analyses of its expression and epigenetic status have shown that SALL4 is de-regulated and aberrantly expressed in various cancers (Review in 64 ) such as leukemia 65 , germ cell tumors 6667 , hepatocellular carcinoma (HCC) 2468 , gastric cancer 20,6973 , colorectal carcinoma 7476 , esophageal squamous cell carcinoma 77,78 , breast cancer 7981 , endometrial cancer 82,83 , lung cancer 8486 and glioma 87 . Functionally, SALL4 is important for the survival 38,80,82,8893 , drug resistance 82,94 and metastasis 69,82 of many of these cancer cells (Figure 4).…”
Section: Sall4 In Cancersmentioning
confidence: 99%